Pancreatic cancer and glucose metabolism - Murat SARUÇ; Mehmet KARAARSLAN; Kemal RASA; Özlem SAYGILI; Ümit İNCE and Çağlar BAYSAL and Parviz M. POUR and Metin ÇAKMAKÇI and Nurdan TÖZÜN (Turkish Journal of Gastroenterology, 2019)
-